2022
DOI: 10.1097/mcc.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Individualized cerebral perfusion pressure in acute neurological injury: are we ready for clinical use?

Abstract: Purpose of reviewIndividualizing cerebral perfusion pressure based on cerebrovascular autoregulation assessment is a promising concept for neurological injuries where autoregulation is typically impaired. The purpose of this review is to describe the status quo of autoregulation-guided protocols and discuss steps towards clinical use. Recent findingsRetrospective studies have indicated an association of impaired autoregulation and poor clinical outcome in traumatic brain injury (TBI), hypoxic-ischemic brain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Differences between TBI and aSAH may require a different strategy for CPPopt calculation and the resulting management, including a reinvestigation of the ±5 mmHg optimal range around the target in aSAH patients. 44 If interpreting PbtO 2 as a surrogate for adequate CBF and considering only PbtO 2 , our results would suggest that the range for CPPopt may be much wider in aSAH, as decrease of PbtO 2 <20 mmHg on cohort level was only observed with deltaCPP <−20 mmHg. However, our data also indicate that hyperperfusion with positive deltaCPP may be tolerated better than hypoperfusion in patients wit aSAH.…”
Section: Discussionmentioning
confidence: 80%
“…Differences between TBI and aSAH may require a different strategy for CPPopt calculation and the resulting management, including a reinvestigation of the ±5 mmHg optimal range around the target in aSAH patients. 44 If interpreting PbtO 2 as a surrogate for adequate CBF and considering only PbtO 2 , our results would suggest that the range for CPPopt may be much wider in aSAH, as decrease of PbtO 2 <20 mmHg on cohort level was only observed with deltaCPP <−20 mmHg. However, our data also indicate that hyperperfusion with positive deltaCPP may be tolerated better than hypoperfusion in patients wit aSAH.…”
Section: Discussionmentioning
confidence: 80%
“…However, personalized patient treatment is possible only when CPPopt is identified in an appropriate time, allowing the implementation of CA-guided management. Failure to identify the CPPopt value is associated with the occurrence of delayed cerebral ischemia in aneurysmal SAH patients 32 .…”
Section: Discussionmentioning
confidence: 99%
“…With all the above, it may be concluded that assessing CPP as the difference between MAP and ICP may not be accurate. Several efforts are being made to provide an accurate estimation and optimization of CPP [47,48]. Unfortunately, optimal CPP is still under development [49,50] and needs dedicated systems that are not widely available especially in LMICs.…”
Section: Cppmentioning
confidence: 99%